2015
DOI: 10.1016/j.jorganchem.2015.07.035
|View full text |Cite
|
Sign up to set email alerts
|

The [closo-B12H11-1-IAr]− zwitterion as a precursor to monosubstituted derivatives of [closo-B12H12]2−

Abstract: Reactions of [closo-B 12 H 12 ] 2with ArI(OAc) 2 in aqueous AcOH in the presence of [NEt 4 ] + or [NHEt 3 ] + give [closo-B 12 H 11-1-IAr]-(1) in 74-95% yield as a white precipitate. The zwitterions decompose in CD 3 CN solutions with rates k = 3.30±0.04×10-4 s-1 (Ar = Ph, 1a[NEt 4 ]) and k = 1.96±0.01×10-4 s-1 (Ar = C 6 H 4 OMe-4, 1b[NEt 4 ]) at 0 o C. Reactions of the zwitterion with Me 2 NCHS and pyridine gave the corresponding products [closo-B 12 H 11-1-SCHNMe 2 ]-(2) and [closo-B 12 H 11-1-NC 5 H 5 ]-(3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…The initial suspension gradually dissolved and the resulting isomeric pyridinium bis‐zwitterions, 1B[ n ]‐ p and 1B[ n ]‐ m , were separated by means of chromatography to give pure products in overall yields of about 14 and 7 %, respectively (Scheme ). The low overall yield is presumably due to the competing rearrangement process and formation of ionic byproducts (cage arylation products), which were immobile on chromatographic supports and were not investigated further.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial suspension gradually dissolved and the resulting isomeric pyridinium bis‐zwitterions, 1B[ n ]‐ p and 1B[ n ]‐ m , were separated by means of chromatography to give pure products in overall yields of about 14 and 7 %, respectively (Scheme ). The low overall yield is presumably due to the competing rearrangement process and formation of ionic byproducts (cage arylation products), which were immobile on chromatographic supports and were not investigated further.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of derivatives 2B[ n ]‐ p was accomplished by starting with either mercaptan [ closo ‐B 12 H 11 ‐1‐SH] 2− ( 4 a ) or its protected forms 4 b and 4 c (Scheme ). Thus, the alkylative cyclization reaction of 4 a ‐[Na], 4 b ‐[Et 4 N], or 4 c ‐[Me 4 N] with dibromide 5 in the presence of an appropriate base, [R 4 N]OH, gave the 4‐pentylthianium derivatives 6 ‐[Et 4 N] or 6 ‐[Me 4 N] in 75–80 % yield, based on 4 a , or about 50 % based on 4 b and 4 c (Scheme ). Subsequent treatment of 6 ‐[R 4 N] with 4‐MeOC 6 H 4 I(OAc) 2 in 70 % aqueous TFA gave a mixture of bis‐zwitterions 7‐ m and 7‐ p (Ar=4‐anisyl).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to now, there are many previous theoretical and experimental studies on the derivatives of the icosahedral [B 12 H 12 ] 2− cluster . For example, Dávalos et al investigated the structures of Li 2 [B 12 H 12 ] (I) and Li[CB 11 H 12 ] (II) using the ESI‐TQ‐FT‐ICR mass spectrometer and computational modeling, and revealed that the oligomerization process of the I and II species has the similar phenomena in the anionic mode.…”
Section: Introductionmentioning
confidence: 99%